On the Uniqueness of the Fock Quantization of the Dirac Field in the Closed FRW Cosmology - Cortez, Jerónimo (2019)
Submitted by VELHINHO (jvelhi@ubi.pt) on 2019-10-11T17:31:47Z No. of bitstreams: 1 AMP_2018_2450816.pdf: 2205925 bytes, checksum: b960e292bd848525d8f1be247aa502f4 (MD5)